[RETRACTION] Factors Related to The Unsuccessful of Exclusive Breastfeeding in Breastfeeding Moms at Yosomulyo Health Center, Metro City - Muflihah, Ima Syamrotul; Anisa, Linda (Jurnal Kesehatan Metro Sai Wawai, 2024)
Introduction: The World Health Organization WHO (2019), recommends to mothers around the world to exclusively breastfeed their babies for the first 6 (six) months after the baby is born to achieve optimal growth, development and health. At the Yosomulyo Health Center, 45.3% were not given exclusive breastfeeding (97 babies out of 214 babies). Objective: The purpose of this study was to determine the factors associated with the failure of exclusive breastfeeding in breastfeeding mothers at the Yosomulyo Health Center. Method: This type of research is quantitative with a cross sectional design. The total population of breastfeeding mothers at the Yosomulyo Health Center is 336 nursing mothers. The sample size was determined based on the Lemeshow formula obtained by 75 respondents. The sampling technique used is simple random sampling. Collecting data using a questionnaire. Results: The results showed that the proportion of breastfeeding mothers: not exclusive breastfeeding was 37.3%, poor knowledge was 18.7%, primiparous parity was 36% and did not support 33.3%. Based on the analysis, it was obtained that each p-value was knowledge with a p-value of 0.009, parity with a p-value of 0.000 and family support with a p-value of 0.000. Conclusion: this study is that there is a relationship between knowledge, parity, and family support with the failure of exclusive breastfeeding for breastfeeding mothers at Yosomulyo Public Health Center, Metro City.